Hospital Admission Patterns in Children with CAH: Admission Rates and Adrenal Crises Decline with Age. (6th January 2016) - Rushworth, R. Louise; Falhammar, Henrik; Munns, Craig F.; Maguire, Ann M.; Torpy, David J.
Abstract : Objective . To examine patterns of hospitalisation for acute medical conditions in children with congenital adrenal hyperplasia (CAH). Design . A retrospective study of hospitalisation using administrative data. Setting . All hospitals in NSW, Australia. Patients . All patients admitted with CAH and a random sample of admissions in patients aged 0 to 18 years without adrenal insufficiency (AI). Main Outcome Measures . Admissions and comorbidities by age and sex. Results . Of 573 admissions for medical problems in CAH children, 286 (49.9%) were in males, and 236 (41.2%) had a principal diagnosis of CAH or had an adrenal crisis (AC). 37 (6.5%) ACs were recorded. An infection was found in 43.5% (n = 249 ) of the CAH patient admissions and 51.7% (n = 1613 ) of the non-AI group, p < 0.001 . Children aged up to one year had the highest number of admissions (n = 149 ) and six ACs (four in males). There were 21 ACs recorded for children aged 1–5 years. Older CAH children had fewer admissions and fewer ACs. No in-hospital deaths were recorded. Conclusions . Admission for medical problems in CAH children declines with age. An AC was recorded in 6.5% of the admissions, with the majority of ACs occurring in the 1 to 5 years age group and there were no deaths.